(untitled) (Research, Society and Development, 2021)
Quantitative assessments of population density in the microbial community in soils are important to establish ecological relationships that occur in the soil and to identify factors that influence the microbiological balance. The objective was to quantify soil microorganisms with potential for agricultural use present in different land use management. The experiment was conducted at the Federal Institute of Science and Technology of Roraima - Campus Novo Paraíso, in the municipality of Caracaraí, Roraima. The experiment was carried out in three areas, soil in intercropping systems, area with gliricidia, orange and banana, area with orange and forest essence and forest. In each area, soil samples were collected at depths of 0-10 and 10-20 cm. The active soil microbiota was evaluated by the surface plating technique. Quantification was obtained by colony forming units per gram of soil (CFU g soil-1). The plates were incubated in a growth oven at 28 ºC for 48 and 96 hours, after which the colony forming units were counted. The quantification of ammonifying, cellulolytic and actinobacteria organisms was obtained by suspending the soil, using specific culture media for each organism. The results show that the soil with the intercropping gliricidia, orange and banana has a greater population of microorganisms (total, cellulolytic, ammonifiers and actinobacteria), showing that it is an alternative for intercropping systems with agricultural crops, providing a greater biodiversity of microorganisms in the soil , in addition to helping in the supply of nitrogen for the species.